Sequência de ensino investigativa para o estudo do efeito fotovoltaico em uma abordagem experimental na perspectiva da teoria de campos conceituais de Vergnaud - CAMPELO, Djamilton Foicinha (2019)
This work discusses the trajectory of the construction of an educational product developed to promote the teaching of the photovoltaic effect for third year classes of high school. This educational product is composed of Investigative Teaching Sequences (SEIs) that are an organized way of promoting teaching, in order to translate physical phenomena into interesting problems for students, which can be solved and whose resolutions lead students towards knowledge scientific. During the research, we developed a SEI that investigates students' prior knowledge about energy conservation and a SEI that studies the photovoltaic effect. The SEIs were developed according to the Theory of Conceptual Fields, where we use simulations and experiments as didactic resources, the evaluation activities included concept maps and questionnaires. After the application of the product, in a third class of the year, we found that analysis of the evaluations demonstrated the development of the technical and scientific language of the students, it was also possible to identify possible operative invariants that appeared in the students' responses in situations proposed to students involving concepts from the conceptual field of energy conversion.